2016
DOI: 10.1039/c6nr03428d
|View full text |Cite
|
Sign up to set email alerts
|

Generalized colloidal synthesis of high-quality, two-dimensional cesium lead halide perovskite nanosheets and their applications in photodetectors

Abstract: All-inorganic cesium lead halide perovskite (CsPbX3, X = Cl, Br, and I) nanocrystals (NCs) are emerging as an important class of semiconductor materials with superior photophysical properties and wide potential applications in optoelectronic devices. So far, only a few studies have been conducted to control the shape and geometry of CsPbX3 NCs. Here we report a general approach to directly synthesize two-dimensional (2D) CsPbX3 perovskite and mixed perovskite nanosheets with uniform and ultrathin thicknesses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
214
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(235 citation statements)
references
References 50 publications
16
214
0
Order By: Relevance
“…As one kind of the perovskites nanomaterials, all-inorganic lead halide perovskites CsPbX 3 (X = I, Br, Cl) are generally recognized as one probable substitute of organic perovskites [15,16]. To date, all-inorganic cesium lead halide perovskite have generated considerable attention because of their higher stability and outstanding optoelectronic properties comparable to the hybrid organic-inorganic perovskites [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As one kind of the perovskites nanomaterials, all-inorganic lead halide perovskites CsPbX 3 (X = I, Br, Cl) are generally recognized as one probable substitute of organic perovskites [15,16]. To date, all-inorganic cesium lead halide perovskite have generated considerable attention because of their higher stability and outstanding optoelectronic properties comparable to the hybrid organic-inorganic perovskites [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This work demonstrates that all-inorganic perovskite CsPbBr 3 NSs have a great potential in photodetector application. Next, Lv et al reported a similar result on CsPbBr 3 NSs photodetectors [56]. Then, our group reported that the responsivity could be improved by the annealing, which was demonstrated to increase coupling energy but decrease exciton binding energy resulting from ligand rearrangement.…”
Section: D Perovskite Photodetectormentioning
confidence: 56%
“…Under illumination of a laser diode at 450 nm, a significant increase in photocurrents was observed. Besides, excellent optical switching and stability of this photodetector were also proved under 1 Hz pulse laser (450 nm) at a fixed light density of 13 mW cm −2 with a bias voltage of 1 V. Through fitting the photocurrent response curve (Figure 7e), the rise time was estimated to be 17.8 ms and the decay times were determined to be 14.7 and 15.2 ms [78]. Li et al used a combined solutionprocessed and vapor-phase conversion method for the synthesis of 2D CH 3 NH 3 PbI 3 nanosheets with a thickness of ~20 nm [79].…”
Section: Two-dimensional Materials For Photodetectormentioning
confidence: 75%
“…Cyan-emitting CsPbBr 3 nanosheets based photodetector was reported by Lv et al [78]. The source-drain current of CsPbBr 3 nanosheet film in the dark was detected to be on the order of 10 −12 A due to the existence of long-chain organic ligands on the nanosheet surface.…”
Section: Two-dimensional Materials For Photodetectormentioning
confidence: 90%
See 1 more Smart Citation